Budgetary resource mobilisation in Asia: growing complexity - Asher, Mukul G. (2003)
Asian countries will need to cope with much greater complexity in both domestic resource mobilisation and in dealing with international tax issues. Fiscal laws and institutions will therefore acquire much greater importance. Capacity to use information technology in fiscal institutions in general, and tax administration and compliance in particular, will acquire greater urgency. Asian countries will also need to consider a regional forum to discuss tax issues and to share tax information. Indigenous fiscal research capability will also need to be strengthened. - Reproduced.
Keywords: Budget - Asia; Budget